Sharing Sadhana: Insights and Inspiration for a Personal Yoga Practice - Bailey, Victoria (Rowman & Littlefield Publishers, 2012)
A daily personal yoga practice, or sadhana, is carried out by yogis and yoginis throughout the world every day. Within western culture our knowledge of yoga and yoga practices has been shaped by lessons and insights provided and shared by well-known yoga teachers and yoga therapists in various traditions. Yet, the consistent message from all these teachers is to maintain your own daily practice – honor your sadhana. Finding and committing yourself to either a particular yogic tradition’s daily discipline or finding the confidence and dedication to create your own yoga practice can be both daunting and challenging to new yoga students while it eventually becomes an essential part of every day for people with an established practice. In Sharing Sadhana, the author provides an overview and outline of what yoga sadhana means within western yoga culture and what it means to prominent and experienced yoga teachers and therapists in the western yoga world. She interviews yoga teachers such as Richard Miller, Nischala Joy Devi, Leslie Kaminoff and other prominent practitioners about their views, advice, and experience of sadhana and what it means to them in their personal daily lives and in their teaching. The book offers a means for these experienced practitioners to share information about their own development of sadhana, to provide insights into their own personal yoga journey as well as sadhana guidance and inspiration to new and seasoned yoga practitioners. It includes the challenges they have faced on their yoga journey and how they have overcome those barriers; their advice to other yoga practitioners; and how their yoga practice has changed over time. Anyone hoping to cultivate a better daily yoga practice will be inspired to begin today.